Service innovation capability for enhancing marketing performance: An SDL perspectives - Lie Heng; Augusty Tae Ferdinand; Nur Afifah; Ramadania Ramadania (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
This study was conducted to propose dan test a conceptual model for solving a research gap on the influence of customer orientation on marketing performance through a strategic bridge variable, service innovation capability, and consumer-centric strategy. We adopt the service-dominant logic as a basis for solving the research gap for its coverage on the value and service value innovation for attracting customers and as a stepping-stone for enhancing marketing performance. Data were collected from 145 service enterprises in Pontianak, West Kalimantan, Indonesia, as our samples for testing the proposed research model, using the software of AMOS-structural equation modeling. The main finding of this study is a strategic path for enhancing marketing performance through customer orientation and the capability for service value-creating.
Keywords: M31; D46; D83; L25; 650; customer orientation; customer-centric strategy; service innovation capability; marketing performance; service-dominant logic; Indonesia